PENGARUH KUALITAS SUMBER DAYA MANUSIA DAN STRATEGI PEMASARAN TERHADAP KEBERLANJUTAN USAHA UMKM DI BREBES - Nur Inayah; Nandang Nandang; Ghia Ghaida Kanita (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
This study aims to determine the effect of human resource quality and marketing strategies on the sustainability of MSME businesses in Cikakak Village, Brebes Regency. The method used is a quantitative research method with descriptive and verification approaches. The population of this study consisted of all MSME players in Cikakak Village, totaling 176 MSMEs. In this study, 44 samples were used, which was 25% of the total population. Data was gathered by distributing questionnaires (questionnaires) with an ordinal scale to the respondents. The results showed that the quality of human resources had a positive and significant influence on business sustainability. In addition, marketing strategy also indicates a positive and considerable influence on business sustainability. These findings emphasize the importance of improving the quality of human resources and effective marketing strategies in supporting business sustainability in the area.